Hubungan Peran Suami Dengan Sikap Ibu Dalam Proses Menyusui Bayi Usia 0-6 Bulan - Agustin, Lia; Dian Rahmawati (JURNAL KEBIDANAN, 2024)
Feeding babies directly from the mother's own breast is breastfeeding. When breastfeeding, mothers need the support of their husband because breastfeeding is not carried out by the mother and baby alone. A husband who is not supportive can affect the mother's emotions, leading baby blues. Emotional support is needed by couples / wives because emotional support affects thoughts, feelings, and sensations that greatly affect the release of oxytocin. Therefore, a husband has a very important role to keep the oxytocin reflex smooth This study aims to determine the relationship between the husband's role and the mother's attitude in the process of breastfeeding babies aged 0-6 months. The research design uses correlational research with a cross-sectional approach. The population and sample were all mothers breastfeeding babies aged 0-6 months at Posyandu in Tales Village. Using a total sampling technique, 30 respondents were obtained. The variables consist of the independent variable, namely the husband's role in mothers breastfeeding babies aged 0-6 months and the dependent variable, namely the mother's attitude in the process of breastfeeding babies aged 0-6 months. Data were collected using a questionnaire on the husband's role in mothers breastfeeding babies aged 0-6 months and the mother's attitude in the process of breastfeeding babies aged 0-6 months. Data processing uses univariate and bivariate analysis with the Chi Square test The research results showed that 13 respondents (43.3%) supported their husband's role with a positive maternal attitude. The statistical test results show that the calculated χ2 is 4.41 which is greater than the table χ2 of 3.841, so H1 is accepted. Based on the data above, it can be concluded that there is a relationship between the husband's role and the mother's attitude in the process of breastfeeding babies aged 0-6 months. From the results of this research, it is hoped that health workers can provide health education through classes for pregnant women by involving their husbands when attending classes for pregnant women. From the statistical test, χ2 calculated 9.03. When compared with χ2 table with a significant level of 5% and n = 30 which is 3.841 it is found that χ2 counts > χ2 table